Quality of life and its relationship to severity of symptoms among patients with end stage renal disease undergoing haemodialysis - J, Vidya; Premkumar, Jayarani; Jesudoss, Illavarasi (Indian Journal of Nursing Sciences, 2024)
Depression disorders are the most frequent mental disorders diagnosed among patients with somatic diseases. The data indicate that depression disorders may affect up to 50% of patients with somatic diseases. The problem of co-morbidity of somatic disease and depression disorder also affects Primary Health Care patients. In the light of available data, the pain syndromes put patients at highest risk of depression, reaching as high as 80%. The concept of quality of life for persons with end stage renal disease is a growing concern among dialysis professionals. Aim: To assess the quality of life and severity of symptoms of patients with end stage renal disease undergoing haemodialysis. To find out the relationship and to determine the association between quality of life and severity of symptoms with selected socio demographic and clinical variables among patients with end stage renal disease undergoing haemodialysis in dialysis unit of a selected hospital in Vellore. Methods: Total enumeration sampling technique was used and a total of 124 samples were assessed using Quality of Life Index Dialysis Version III (QLI-D) and Dialysis symptom Index (DSI). Data was collected by self-administered questionnaire. Results: The findings showed that most of the subjects had a good quality of life (70.2%) and most of them experienced less severe symptoms (97.6%). There was also a significant negative correlation between quality of life and severity of symptoms (p<0.01). Conclusion: The result of this study showed patients QOL is an important indicator of the effectiveness of the medical care that they receive.